2022
DOI: 10.1038/s41586-022-05015-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interplay of an assembly machinery for nitrous oxide reductase

Abstract: Emissions of the critical ozone-depleting and greenhouse gas nitrous oxide (N2O) from soils and industrial processes have increased significantly over the last decades 1-3 . As the final step of bacterial denitrification, the critical greenhouse gas N2O is reduced to chemically inert N2 (ref. 1,4) in a reaction catalyzed by the copper-dependent nitrous oxide reductase (N2OR) 5 . The assembly of its unique [4Cu:2S] active site cluster CuZ requires both the ATP-bindingcassette (ABC) complex NosDFY and the membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…The latter is reminiscent of our 1-hole complex, which indeed undergoes a structural rearrangement from a seesaw to a square planar core geometry. Though the protein environment was suggested to be strained, the flipping of some histidine rings as well as a conformational switch of the active site relevant to its function has indeed been observed for these N 2 OR enzymes , and has been suggested for their Cu A site by theoretical calculations as well . Furthermore, a complex network of hydrogen bonds involving the protein environment has been suggested to determine the orientation of the histidine side chains .…”
Section: Discussionmentioning
confidence: 95%
“…The latter is reminiscent of our 1-hole complex, which indeed undergoes a structural rearrangement from a seesaw to a square planar core geometry. Though the protein environment was suggested to be strained, the flipping of some histidine rings as well as a conformational switch of the active site relevant to its function has indeed been observed for these N 2 OR enzymes , and has been suggested for their Cu A site by theoretical calculations as well . Furthermore, a complex network of hydrogen bonds involving the protein environment has been suggested to determine the orientation of the histidine side chains .…”
Section: Discussionmentioning
confidence: 95%
“…membrane. 73 Recently, Mu ¨ller et al found that this step is assisted by two membrane proteins NosL and NosDFY (Fig. 6B).…”
Section: Catassemblers For the Assembly Of Biomacromolecular Complexesmentioning
confidence: 88%
“…Soil mineral N is one of the most important nutrients to favor soil microbial growth and improve plant production (Fan et al, 2022; Müller et al, 2022). Significantly increased soil NH 4 + –N was shown in the DA and PA treatments (Table 1), and these results might be accounted for different reasons: (1) nitrification inhibitor DMPP inhibited soil nitrification and then directly enhanced soil NH 4 + –N but decreased NO 3 − –N content (Hargreaves et al, 2021; Jin et al, 2022; Meng et al, 2021; Wang, Liu, et al, 2021), and previous studies suggested that the PSB inoculation also contributed to organic N mineralization (Dong et al, 2022; Jatana et al, 2020; Liu, Bai, Wang, Zhang, et al, 2022); (2) organic residues decomposition by soil microbes might elevate soil NH 4 + –N content (Zhang et al, 2021), which was supported by positive correlations between the soil NH 4 + –N and Peptostreptococcus , Entransia , and Candidatus_Nucleicultrix in this study (Figure 6); and (3) enhanced soil protease activity played a functional role for improving soil NH 4 + –N content (Greenfield et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Mineral nitrogen (N) is closely related to microbial activity and agricultural crop yield, but low N nutrition supply generally occurs to impair soil microbial biomass and activity and crop yield (Fan et al, 2022; Müller et al, 2022). Protein is regarded as one of the most abundant organic molecules containing numerous N in the soil, which could be hydrolyzed by protease activity to accelerate N metabolism and cycling (Geisseler et al, 2010; Greenfield et al, 2021).…”
Section: Introductionmentioning
confidence: 99%